2014
DOI: 10.4253/wjge.v6.i11.549
|View full text |Cite
|
Sign up to set email alerts
|

Hyoscine for polyp detection during colonoscopy: A meta-analysis and systematic review

Abstract: AIM:To assess the role of hyoscine for polyp detection during colonoscopy. METHODS: Studies (randomized controlled trials orRCTs) that compared the use of hyoscine vs no hyoscine or placebo for polyp detection during colonoscopy were included in our analysis. A search on multiple databases was performed in September 2013 with search terms being "hyoscine and colonoscopy", "hyoscine and polyp", "hyoscine and adenoma", "antispasmotic and colonoscopy", "antispasmotic and adenoma", and "antispasmotic and polyp". J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Therefore, giving antispasmodic agents to minimize technical difficulties and patient discomfort is still controversial. Recently, several meta‐analyses on the use of antispasmodic agents during colonoscopy for lesion detection have been published . None of them concluded that the use of antispasmodic agents improved the detection rate of either adenomas or polyps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, giving antispasmodic agents to minimize technical difficulties and patient discomfort is still controversial. Recently, several meta‐analyses on the use of antispasmodic agents during colonoscopy for lesion detection have been published . None of them concluded that the use of antispasmodic agents improved the detection rate of either adenomas or polyps.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several meta-analyses on the use of antispasmodic agents during colonoscopy for lesion detection have been published. [25][26][27][28] None of them concluded that the use of antispasmodic agents improved the detection rate of either adenomas or polyps. However, one RCT showed that hyoscine butylbromide increased the number of polyps identified per patient.…”
Section: Grade Of Recommendationmentioning
confidence: 99%
“…A recent meta-analysis based upon the finding of eight RCTs conducted in Europe, Asia and Australia concluded that hyoscine use in patients undergoing colonoscopy does not appear to significantly increase the detection of adenomas [10]. Contrary to this, a study examining the use of different antispasmodic that is applied topically during the procedure: L-menthol (an organic compound found in peppermint oil), demonstrated an improved ADR [11].…”
Section: Use Of Antispasmodics and Sedationmentioning
confidence: 96%
“…165,166 Hyoscine butylbromide may increase mucosal view and polyp detection. 167 No fewer than four systematic reviews and metaanalyses [168][169][170][171] have been published on the eight trials in this area, 154,[172][173][174][175][176][177][178] which draw differing conclusions. While metaanalysis does not demonstrate increased polyp detection with hyoscine butylbromide, several of the analyzed studies 154,178 did not have polyp detection or adenoma detection as their primary endpoint, and some are of low quality.…”
Section: Retroflexionmentioning
confidence: 99%